Network analysis of Contingencies of Self-Worth Scale in 680 university students. (February 2019) - Briganti, Giovanni; Fried, Eiko I.; Linkowski, Paul
Highlights: This is the first time network analysis is applied to self-worth research. Academic competence and appearance are the most interconnected domains in the network. Competition and academic competence share the strongest connection in the network. God's love is a disconnected domain in the self-worth network. Abstract: This study investigates the Contingencies of Self-Worth Scale (CSWS) in a sample of 680 university students from a network perspective. We estimated regularized partial correlations among seven CSWS domains: family support, competition, appearance, God's love, academic competence, virtue and other's approval. Competition – academic competence and competition – appearance represent the strongest connections in the network. Mean node predictability (shared variance with surrounding nodes) is 0.25. Appearance and academic competence were the most central (i.e., interconnected) domains in the network. Future studies should explore the network structure of self-worth in other healthy adult samples, and also in people with psychopathology. We provide the anonymized dataset as well as the full code in the supplementary materials to ensure complete reproducibility of the results.